HUBUNGAN DUKUNGAN PMO DAN KETERATURAN MINUM OBAT DENGAN KEGAGALAN KONVERSI TB PARU - Siti Shofiya; Novita Sari (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2016)
Objective: to analyze PMO support and medication adherence that associated with pulmonary TB conversion failure in the intensive phase of treatment in Surabaya. Methods: The type of this research is case-control design. The object of this study is pulmonary TB patients who experienced conversion failure in the intensive phase of category 1 in Surabaya on 2015. Samples were taken by simple random sampling method. Total sample of the research used a ratio of 1: 2 that was 27 case samples and 54 control samples. Simple random sampling method was used. The independent variables included PMO support and medication adherence. Data analysis were using chi-square test. Results: The results showed that independent variables have no relationship with conversion failure (p value < 0,05). PMO support has p-value < 0,05 (0,59) and medication adherence has p-value < 0,05 (0,46). Conclusion: The Only comorbiditeis that have relationship with conversion failure.